2004
DOI: 10.1289/ehp.7295
|View full text |Cite
|
Sign up to set email alerts
|

The Sources of Inflammatory Mediators in the Lung after Silica Exposure

Abstract: The expression of 10 genes implicated in regulation of the inflammatory processes in the lung was studied after exposure of alveolar macrophages (AMs) to silica in vitro or in vivo. Exposure of AMs to silica in vitro up-regulated the messenger RNA (mRNA) levels of three genes [interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein-2 (MIP-2)] without a concomitant increase in the protein levels. AMs isolated after intratracheal instillation of silica up-regulated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 67 publications
2
41
1
Order By: Relevance
“…20,21 A study examining the effect of silica exposure on the production of inflammatory mediators in the lung has shown upregulation of IL-6 and MCP-1 in alveolar macrophages and fibroblasts. 22 Therefore, in the present study the increased levels of Ccl2 and IL-6 mRNA expression in the lungs of CB-treated rats may account for the differences in the circulating levels of IL-6 and MCP-1 between the 2 groups. Cytokines associated with inflammation are known to trigger the production of acute-phase proteins, with IL-6 being the major stimulator of CRP synthesis in the liver.…”
Section: Discussionmentioning
confidence: 57%
“…20,21 A study examining the effect of silica exposure on the production of inflammatory mediators in the lung has shown upregulation of IL-6 and MCP-1 in alveolar macrophages and fibroblasts. 22 Therefore, in the present study the increased levels of Ccl2 and IL-6 mRNA expression in the lungs of CB-treated rats may account for the differences in the circulating levels of IL-6 and MCP-1 between the 2 groups. Cytokines associated with inflammation are known to trigger the production of acute-phase proteins, with IL-6 being the major stimulator of CRP synthesis in the liver.…”
Section: Discussionmentioning
confidence: 57%
“…It is well accepted that the proinflammatory functions of IL-17 and -22 are due to their capacities to stimulate neutrophilic factors released by epithelial cells. KC and MIP-2, two IL-8-related cytokines and powerful neutrophil chemoattractants, are produced by alveolar epithelial cells after silica exposure (52,53), and neutralization experiments showed that both chemokines play an important role in the accumulation of lung neutrophils in silica-treated rats (54). The reduced production of KC and MIP-2 in the lungs of silica-treated IL-17R-deficient mice newly supports that, in addition to silica, IL-17A-producing T lymphocytes exacerbate proinflammatory functions of epithelial cells during silicosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, divergence is thought to have been caused either by control of translation into proteins or control of protein disintegration. There are reports 14,15) on the divergence of expression for other genes caused by exposure to silica. Williams et al 14) found that the mRNA levels of TGF accelerated in epithelial cell lines exposed to silica while protein levels did not.…”
Section: Discussionmentioning
confidence: 99%